\[\boxed{\mathbf{1235}\mathbf{.}}\]
\[1)\ 6\sin^{2}x - \cos x + 6 = 0\]
\[6\left( 1 - \cos^{2}x \right) - \cos x + 6 = 0\]
\[6 - 6\cos^{2}x - \cos x + 6 = 0\]
\[6\cos^{2}x + \cos x - 12 = 0\]
\[Пусть\ y = \cos x:\]
\[6y^{2} + y - 12 = 0\]
\[D = 1^{2} + 4 \bullet 6 \bullet 12 = 1 + 288 =\]
\[\text{=}289\]
\[y_{1} = \frac{- 1 - 17}{2 \bullet 6} = - \frac{18}{12} = - \frac{3}{2}\text{\ \ }и\ \]
\[\ y_{2} = \frac{- 1 + 17}{2 \bullet 6} = \frac{16}{12} = \frac{4}{3},\]
\[|y| > 1 - корней\ нет.\]
\[Ответ:\ \ корней\ нет.\]
\[2)\ 8\cos^{2}x - 12\sin x + 7 = 0\]
\[8\left( 1 - \sin^{2}x \right) - 12\sin x + 7 = 0\]
\[8 - 8\sin^{2}x - 12\sin x + 7 = 0\]
\[8\sin^{2}x + 12\sin x - 15 = 0\]
\[Пусть\ y = \sin x:\]
\[8y^{2} + 12y - 15 = 0\]
\[D = 12^{2} + 4 \bullet 8 \bullet 15 = 144 +\]
\[+ 480 = 624\]
\[y = \frac{- 12 \pm 4\sqrt{39}}{2 \bullet 8} = \frac{- 3 \pm \sqrt{39}}{4}.\]
\[Первое\ уравнение:\]
\[\sin x = \frac{- 3 - \sqrt{39}}{4} - корней\ \]
\[нет.\]
\[Второе\ уравнение:\]
\[\sin x = \frac{- 3 + \sqrt{39}}{4}\]
\[x = ( - 1)^{n} \bullet \arcsin\frac{\sqrt{39} - 3}{4} + \pi n.\]
\[Ответ:\ \ ( - 1)^{n} \bullet\]
\[\bullet \arcsin\frac{\sqrt{39} - 3}{4} + \pi n.\]